Return and risk of human capital contracts - Tim A. Kroencke; Grit Muehler; Maresa Sprietsma (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2013)
Human capital contracts give private investors the right to share of students' future earnings in return for a financial contribution during their studies. Although still rarely used, human capital contracts could not only help to completement limited public funding for higher education but might also be an alternative to traditional financial assets. Using a dataset covering 1% of German households for the period 1995-2009, we analyse the return and risk properties that can be expected from human capital contracts. We find that funds of human capital contracts provide low risk exposures to stocks and bonds. As a result, risk-adjusted returns of funds of human capital contracts are signicantly positive under fairly weak conditions. Thus, human capital contracts potentially offer large diversification benefits for investors and might be a way to improve the state's educational budget
urn:nbn:de:bsz:180-madoc-353004
Keywords: I21; J24; G11; G12; 330; human capital returns; human capital contracts; risk and return of non-traded assets; mean-variance spanning tests